Wet gas measurement - Henry, M; Tombs, MS (Canadian Intellectual Property Office, 2008)
A first apparent property of a multi-phase process fluid is determined based on the motion of the vibratable flowtube. One or more apparent intermediate values associated with the multi-phase process fluid are determined based on the first apparent property. A measure of wetness of the multi-phase process fluid is determined based on a mapping between one or more of the apparent intermediate values and the measure of wetness. A second apparent property of the multi-phase process fluid is determined using the differential pressure flowmeter. One or more phase-specific properties of the multi-phase process fluid is determined based on the measure of wetness and the second apparent property.